COVID-19 symptoms at hospital admission vary with age and sex - Abdukahil, Sheryl Ann (2021)
Funding This work was supported by the Department for International Development and Wellcome Trust [215091/Z/18/Z]; the Bill and Melinda Gates Foundation [OPP1209135]. Country-specifc support was provided by the Canadian Institutes of Health Research Coronavirus Rapid Research Funding Opportunity [OV2170359]; the Health Research Board Ireland [CTN Award 2014-012]; National Institute for Health Research (NIHR) [award CO-CIN-01]; the Medical Research Council (MRC) [grant MC_PC_19059]; the NIHR Health Protection Research Unit (HPRU) in Emerging and Zoonotic Infections at University of Liverpool in partnership with Public Health England (PHE), in collaboration with Liverpool School of Tropical Medicine and the University of Oxford [award 200907]; NIHR HPRU in Respiratory Infections at Imperial College London with PHE [award 200927]; Liverpool Experimental Cancer Medicine Centre [grant reference C18616/ A25153]; NIHR Biomedical Research Centre at Imperial College London [IS-BRC-1215-20013]; EU Platform for European Preparedness Against (Re-)-)emerging Epidemics (PREPARE) [FP7 project 602525]; National Institutes of Health (NIH) [UL1TR002240]; and NIHR Clinical Research Network infrastructure support. We acknowledge the generous support of all ISARIC Partners who have contributed data and expertise to this analysis, with or without dedicated funding. The views expressed are those of the authors and not necessarily those of the funders or institutions listed above.